If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 3 + -2 = -6z + -7 Reorder the terms: 3 + -2 + 4z = -6z + -7 Combine like terms: 3 + -2 = 1 1 + 4z = -6z + -7 Reorder the terms: 1 + 4z = -7 + -6z Solving 1 + 4z = -7 + -6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6z' to each side of the equation. 1 + 4z + 6z = -7 + -6z + 6z Combine like terms: 4z + 6z = 10z 1 + 10z = -7 + -6z + 6z Combine like terms: -6z + 6z = 0 1 + 10z = -7 + 0 1 + 10z = -7 Add '-1' to each side of the equation. 1 + -1 + 10z = -7 + -1 Combine like terms: 1 + -1 = 0 0 + 10z = -7 + -1 10z = -7 + -1 Combine like terms: -7 + -1 = -8 10z = -8 Divide each side by '10'. z = -0.8 Simplifying z = -0.8
| 0.2(x+60)+0.6x=28 | | X^2+3x+2=5x+5 | | 0.5x+x=15 | | -3/14+x=-2/15 | | W*2(w*2+5)*2=250 | | 4x-8=128 | | 4x-8=52 | | 2b-5-11b-9= | | 8/x=10/25 | | 9-4t=10 | | 6(x+2)/4=4x-1 | | 4a+5-10a= | | -3(2x-8)=-30 | | -12+x=50 | | -2x+(-2)=0 | | h(t)=-16t^2+15t+48 | | 4x^2-40x+78=0 | | 3.25*6.50=21 | | 8xwhat=48 | | 8x-15-3x=5 | | .25(x+8)=.33(x+27) | | 21+40=61 | | 50=18w-10-6w | | -5(4b+2)+(21b-6)=0 | | 4x-2-3x=6 | | -41/6x=25 | | 3(-2x+1)=29 | | ln(15)=ln(4)+ln(x+6) | | (6-4x)*(5-2x)=6 | | (36x^2)+(36y^2)-144=0 | | -6n=-31.26 | | y=35000+.45x |